Barium Titanate Nanoparticles for Biomarker Applications. (September 2015) - Matar, O; Posada, O M; Hondow, N S; Wälti, C; Saunders, M; Murray, C A; Brydson, R M D; Milne, S J; Brown, A P
Abstract: A tetragonal crystal structure is required for barium titanate nanoparticles to exhibit the nonlinear optical effect of second harmonic light generation (SHG) for use as a biomarker when illuminated by a near-infrared source. Here we use synchrotron XRD to elucidate the tetragonal phase of commercially purchased tetragonal, cubic and hydrothermally prepared barium titanate (BaTiO3 ) nanoparticles by peak fitting with reference patterns. The local phase of individual nanoparticles is determined by STEM electron energy loss spectroscopy (EELS), measuring the core-loss O K -edge and the Ti L 3 -edge energy separation of the t 2 g, eg peaks. The results show a change in energy separation between the t 2 g and eg peak from the surface and core of the particles, suggesting an intraparticle phase mixture of the barium titanate nanoparticles. HAADF-STEM and bright field TEM-EDX show cellular uptake of the hydrothermally prepared BaTiO3 nanoparticles, highlighting the potential for application as biomarkers.